Mental health of informal caregivers - Rajović Tatjana; Milić Nataša (Medicinski Podmladak, 2022)
The aging society is facing an important public health problem related to provision of care to older and dependent people. The care provided on a daily basis includes a range of different social and health services, as well as the provision of emotional support to people who are not capable to function independently. Activities important for day by day functioning, such as bathing, dressing, feeding, shopping and health monitoring are only part of the responsibilities and obligations that the "invisible workforce", i.e. informal caregivers, must provide. Even though, regardless of the heavy price informal caregivers often pay with their economic and health status, they still remain a blind spot in public policies. An informal caregiver provides ongoing care and assistance, without receiving payment, to family members and friends who need support due to physical, cognitive or mental problems. Depression is one of the most common problems experienced by informal caregivers and it is estimated that a large number, in the range of 40% to about 70% of all informal caregivers have depression symptoms. The COVID-19 pandemic has certainly left its mark on physical health, however, as the pandemic moves forward, it has began to show an ever increasing impact on the mental health of people around the world, where informal caregivers fall into a particularly vulnerable category. Particularly those informal caregivers who provide long-term help to a member of the family, became of an increased risk of emotional and physical exhaustion due to the burden of care, reduced services, as well as the relocation to consulting by telephone and the digital sphere. While some some of them managed to cope with stress and became resilient, others did not and the increasing psychological pressure led to the development of depression symptoms.